Genitalic structure and copulation in Paralabella dorsalis (Dermapter: Labbidae) - Briceño, R D (1997)
The genitalia of 30 females and 30 males in Paralabella dorsalis were dissected and drawn using a camera lucida. Between 1O and 20 min rrom the initintioo of copulation 20 pairs were frozen with ethyichloride, and the females were tllen dissected irnmediately to determine the location of male genitalic parts. The maJe genitalia consist of a subcylindrical penís wíth a single medial distru lobe, omamented arcas witn sclerotized spines in me mió section. The cloacal opening of (he female is simple with spines sUl'rounding the gonopore. rile spermatheca is a tbin, coiled tube. During copulation part of the male gemta/k teeth reach the sclerotized female spines. The tip of the virga reaches t.he opening of the spelmatheca, wnere sperm deposition occurs.